2007
DOI: 10.1038/sj.leu.2404682
|View full text |Cite
|
Sign up to set email alerts
|

A different schedule of zoledronic acid can reduce the risk of the osteonecrosis of the jaw in patients with multiple myeloma

Abstract: Osteonecrosis of the jaw (ONJ) is a reported complication of bisphosphonate use. The incidence ranges between 6 and 13% and seems to be higher in people treated with zoledronic acid (ZA) than with pamidronate. We retrospectively evaluated the incidences of ONJ and skeletal-related events (SRE) in 106 patients with multiple myeloma divided in two groups according to the schedule of administration of bisphosphonates: 51 received monthly administrations until tolerated (group A, standard schedule), 55 were treate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
0
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(62 citation statements)
references
References 14 publications
2
56
0
4
Order By: Relevance
“…3,12,13 The results of this study (9.7%) fall within the reported range. Risk factors for BRONJ include: recent dento-alveolar surgery, 2,14,15 bisphosphonate exposure and frequency of administration, 16,17 potency of the drug, 16,18 local anatomy (mandible more common than maxilla and more common in areas with thin oral mucosa like tori and mylohyoid ridge), 12 oral disease, systemic conditions and co-morbidities, 12,18 and finally genetic factors. 19 All four cases of confirmed BRONJ in this study had dental co-morbidities as inciting event.…”
Section: Discussionmentioning
confidence: 99%
“…3,12,13 The results of this study (9.7%) fall within the reported range. Risk factors for BRONJ include: recent dento-alveolar surgery, 2,14,15 bisphosphonate exposure and frequency of administration, 16,17 potency of the drug, 16,18 local anatomy (mandible more common than maxilla and more common in areas with thin oral mucosa like tori and mylohyoid ridge), 12 oral disease, systemic conditions and co-morbidities, 12,18 and finally genetic factors. 19 All four cases of confirmed BRONJ in this study had dental co-morbidities as inciting event.…”
Section: Discussionmentioning
confidence: 99%
“…By literature data, the potential of development of osteonecrosis as a result of administration of amino-bisphosphonates (Zoledronate and Pamidronate) is greater than that of non-aminobisphosphonates (Clodronate) [6,7]. Perhaps the most important factor for the occurrence of bisphosphonate-related osteonecrosis of the jaw is the duration of treatment [4,8,9]. Badros et al [10] suggested that the risk of developing bisphosphonate-related necrosis of the jaw was increased by 57% with each year after diagnosing multiple myeloma and starting its treatment.…”
Section: Triggering Factors Risk Factors Associated With Bisphosphonamentioning
confidence: 99%
“…A retrospective study of a different dose schedule in 106 patients with multiple myeloma found that the risk of developing ONJ was eight-fold lower in patients receiving iv bisphosphonates (zoledronate and/or pamidronate) at a reduced frequency (monthly administration during the first year and then every 3 months) compared to patients receiving iv bisphosphonates according to the monthly administrations (Corso et al, 2007). Further studies are required to optimise the treatment regimen (dose, frequency and duration of therapy) for iv bisphosphonates in order to reduce the risk of ONJ while maintaining clinical efficacy.…”
Section: Optimising the Treatment Regimen For IV Bisphosphonatesmentioning
confidence: 99%